(untitled) (Journal of Modern Mechanical Engineering and Technology, 2022)
Abstract: The proper screw rotor cutting process is essential to obtain a precise rotor profile; however, it is a costly and high hazard if studied in a practical method. This study introduces an analytical screw cutting method to ensure the cutting process is running well and acquire the expected rotor profile. Two distinct cutter types, a cutter with a single curve and multiple inserts cutting edge, were applied. The analytical screw cutting method was developed according to the cutter-workpiece engagement model. The result reveals that the analytical screw cutting model using various cutters can generate identical simulated profiles and close to the original rotor profile. In addition, the virtual machining verification using VERICUT software was conducted to evaluate the proposed method. Conclusively, the analytical screw cutting method is reliable and realistic to be applied in screw rotor milling.